Protection of Indigenous Peoples (Local Beliefs) in the Context of Human Rights in Indonesia - Naufal Khaidar; Maulana Adi Nugraha (Contemporary Issues on Interfaith Law and Society, 2022)
The removal of the religious column from the national identity card has sparked considerable debate, with proponents and opponents expressing divergent viewpoints. On one hand, the move is seen as a step towards inclusivity, as many belief systems find it challenging to fit within the confines of the religious classification. Conversely, critics argue that replacing religion with belief may still introduce bias and fail to fully protect diverse belief systems. This study aims to analyze the implications of removing the religion identity from the national identity card, employing a literature review and comparative analysis of relevant laws and regulations pertaining to freedom of religion and belief in both national and international legal frameworks. Initial motivations for eliminating the religion column were rooted in the desire to accommodate adherents of various belief systems, eventually evolving into broader discussions about removing the column altogether for all religious communities in Indonesia. Following Constitutional Court Decision No. 97/PUU-XIV/2016, individuals professing a belief system were granted the option to specify their beliefs on their identity cards. This decision marked a significant milestone, reflecting the government's commitment to ensuring equal rights for all Indonesian citizens, irrespective of their religious or belief affiliations. Moreover, legal guarantees for freedom of religion and belief are enshrined in Article 28 E and 29(2) of the 1945 Constitution, as well as in national legislation such as the Law on Human Rights and international agreements like the International Covenant on Civil and Political Rights (ICCPR).